2011
DOI: 10.1292/jvms.10-0259
|View full text |Cite
|
Sign up to set email alerts
|

A Surge-Like Increase in Luteinizing Hormone Preceding Musth in a Captive Bull African Elephant (Loxodonta africana)

Abstract: ABSTRACT. This study was conducted to determine the correlation between reproductive hormones and musth in a male African elephant. Changes in circulating luteinizing hormone (LH), follicle stimulating hormone (FSH), testosterone and immunoreactive (ir-) inhibin and the degree of musth were evaluated for 4 years. LH increased 4 weeks before musth began. The highest concentrations of testosterone and ir-inhibin were observed from April to October. There were positive correlations among testosterone, ir-inhibin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Previous reports have shown that the serum inhibin levels were parallel with progesterone throughout the estrous cycle in Asian elephants [Brown et al, ; Kaewmanee et al, ]. Kaewmanee et al demonstrated that the immunolocalization of inhibin α, βA, and βB subunits were detected in both granulosa cells of antral follicles and luteal cells in the ovary of an Asian elephant [Kaewmanee et al, ]. These findings strongly suggested that CLs and follicles were the source of circulating inhibin during the estrous cycle in the Asian elephants.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous reports have shown that the serum inhibin levels were parallel with progesterone throughout the estrous cycle in Asian elephants [Brown et al, ; Kaewmanee et al, ]. Kaewmanee et al demonstrated that the immunolocalization of inhibin α, βA, and βB subunits were detected in both granulosa cells of antral follicles and luteal cells in the ovary of an Asian elephant [Kaewmanee et al, ]. These findings strongly suggested that CLs and follicles were the source of circulating inhibin during the estrous cycle in the Asian elephants.…”
Section: Introductionmentioning
confidence: 82%
“…The serum concentrations of ir‐inhibin were determined by RIA based on the bovine inhibin RIA previously described [Kaewmanee et al, , ; Hamada et al, ], using antisera against bovine inhibin (TNDH‐1, Laboratory of Veterinary Physiology, Tokyo University of Agriculture and Technology) and bovine 32 kDa inhibin for both iodination and standard, respectively. Since inhibin antiserum (TNDH‐1) cross‐reacts with 26 kDa α monomer [Kaneko et al, ; Medan et al, ] inhibin are referred to as immunoreactive (ir‐) inhibin.…”
Section: Methodsmentioning
confidence: 99%
“…Although research regarding the role of inhibin in both African and Asian female elephants has been previously reported [ 7 , 13 , 24 ], only males in the African species have been studied [ 8 , 12 ]. The present study determined the immunolocalization of inhibin/activin subunits in the testes of adult male Asian elephants.…”
mentioning
confidence: 99%
“…Moreover, the inhibin secretory pattern in male African elephants has been previously reported by Kaewmanee et al . [ 8 ], who found that the level of circulating immunoreactive (ir)-inhibin in male African elephants was correlated with the degree of musth and testosterone level, with the latter being higher in the musth than in the pre- and non-musth stages. The authors suggest that the increasing level of (ir)-inhibin and testosterone during the musth stage resulted from the stimulation of high luteinizing hormone (LH) and FSH during the pre-musth stage [ 8 ].…”
mentioning
confidence: 99%
“…Frequent sampling of Asian elephant bulls has further demonstrated that pulses of testosterone closely follow those of LH (w1 pulse/ 3 hours) [13]. In a long-term study (4 years) of one African bull, serum LH increased about 4 weeks before the onset of musth and was maintained for approximately 5 weeks and was considered likely to be responsible for triggering the rise in testosterone [14]. The temporal relationship between aggressive behaviors and androgen production during musth suggests that the two are linked although the regulatory mechanisms are unknown.…”
Section: Introductionmentioning
confidence: 99%